Recent Advances in Scar Biology - Rei Ogawa (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Scars develop in the final stage of wound healing. Wound healing and scarring involve complex biological pathways, and the exact mechanisms by which they are initiated, evolved, and regulated remain to be fully elucidated. Scarless wound healing is a major goal of medical science. To achieve this goal, it is necessary to elucidate the relevant clinical, histopathological, and molecular manifestations of scars, and to understand how these manifestations relate to each other. This Special Issue covers a selection of recent research topics and current review articles in the field of scar research for all kinds of tissues and organs.